EFFECT OF CIDR WITH OR WITHOUT GnRH AND DOUBLE PGF2α BASED ESTRUS SYNCHRONIZATION PROTOCOLS ON ESTRUS RESPONSE AND PREGNANCY PER AI IN NON-DESCRIPT COWS OF THE PUNJAB - M. S. Haider; M. Bilal; H. Ahmed; M. Anwar; A. Sattar; S. M. H. Andrabi1 (Journal of Animal and Plant Sciences, 2017)
Two experiments were conducted to analyze the effect of controlled internal drug release device (CIDR) containing 1.38 g progesterone (P4) with or without gonadotropin releasing hormone (GnRH) and double prostaglandin (PGF2α) on estrus response and pregnancy per AI in non-descript cows. In exp 1, cows in 2nd to 3rd lactation (n=80) were randomly divided into two groups as CIDR alone (n=40; CIDR inserted on D0, PGF2α analogue administered on D6 and CIDR removed on D7) and CIDR along with GnRH (n=40; GnRH analogue administered at D0 and rest of the scheme was same as in CIDR alone) during the low breeding season. Whereas, in exp 2, cows in 2nd to 4th lactation (n=67) were distributed into two groups as CIDR (n=33; CIDR inserted on D0, PGF2α analogue administered on D6 and CIDR removed on D7) and double PGF2α group (n=34; PGF2α analogue administered twice with 14 days interval) during the peak breeding season. Artificial inseminations (AI) were performed at 58 h after CIDR removal in all CIDR treated cows and upon detected estrus in the double PGF2α group of exp 2. Pregnancy was diagnosed at 50 days post AI through rectal palpation. Estrus response did not differ significantly in both groups of exp 1(82.5 vs. 90%) and exp 2 (76 vs. 76%), however, estrus intensity differed (P=0.01; 3.02 ± 0.10 vs. 3.32 ± 0.12) between groups of exp 1. The pregnancy per AI did not differ (P>0.05) between CIDR alone (52%) and CIDR along with GnRH (58%) treated cows of exp 1; whereas, it tended to be higher (P=0.19) in CIDR treated cows (64%) as compared to double PGF2α (46%) of exp 2. It is concluded that CIDR-based estrus synchronization protocol improves the reproductive efficiency of non-descript cows during the low and peak breeding seasons.
Keywords: Non-descript cows; CIDR; PGF2α; Estrus synchronization; Artificial insemination; Pregnancy per AI